Methodical approach to the choice of a business management strategy within the framework of a change in commercial activities - Alazzam, Farouq Ahmad Faleh; Tubishat, Bassam Mustafa Abdel-Rahman; Storozhuk, Oksana; Poplavska, Olga; Zhyvko, Zinaida (Business: Theory and Practice, 2024)
The main purpose of the article is the formation of new strategies in business management with changes in commercial activities. The object of the study is the system of commercial activity and possible changes in it. The scientific task is the definition of a new methodological approach to the formation of new strategies in business management with changes in commercial activity. The research methodology involves the use of a modern method for modeling strategies in business management with changes in business activities. As a result, we presented a methodical approach to the formation of business management strategies in the face of changes in commercial activities. The author’s vision of how the stages of forming the main business management strategy through block-object-oriented modeling should look graphically and schematically was presented.  Each of its blocks involves many processions and actions aimed at changes in commercial activity. The innovative novelty of our study lies in the presented methodological approach to the formation of a business management strategy within the framework of changes in commercial activity.